Cell-Based NIPT Detects 47,XXY Genotype in a Twin Pregnancy - Jeppesen, Line Dahl; Hjortshøj, Tina Duelund; Hindkjær, Johnny; Hatt, Lotte; Petersen, Olav Bjørn; Singh, Ripudaman; Schelde, Palle; Andreasen, Lotte; Christensen, Rikke; Lildballe, Dorte L.; Vogel, Ida (Frontiers in Genetics, 2022)
Background: The existing risk of procedure-related miscarriage following invasive sampling for prenatal diagnosis is higher for twin pregnancies and few women are reluctant to test these difficultly obtained pregnancies invasively. Therefore, there is a need for noninvasive testing options that can test twin pregnancies at an early gestational age and ideally test the twins individually. Case presentation: A pregnant woman opted for cell-based NIPT at GA 10+5, which was provided in a research setting because an ultrasound scan showed that she carried dichorionic twins. As a part of the public antenatal care, she had a normal first trimester ultrasound scan and risk assessment for trisomies at GA 12+5. Materials and Methods: Fifty mL of peripheral blood was sampled, and circulating fetal cells were enriched and isolated. Individual cells were subject to whole-genome amplification and STR analysis. Three fetal cells were analyzed by chromosomal microarray (aCGH). Results: We identified 20 fetal cells all sharing the same genetic profile, which increased the likelihood of monozygotic twins. aCGH of three fetal cells showed the presence of two X chromosomes and a gain of chromosome Y. CVS from both placentae confirmed the sex chromosomal anomaly, 47,XXY and that both fetuses were affected. Conclusion: NIPT options can provide valuable genetic information to twin pregnancies that help the couples in their decision-making on prenatal testing. Little has been published about the use of cell-based NIPT in twin pregnancies, but the method may offer the possibility to obtain individual cell-based NIPT results in dizygotic twins.